Implementasi Internal Wireless Roaming Menggunakan Mikrotik Wireless Distribution System (WDS) Pada STMIK Lombok - Mohammad Taufan Asri Zaen; Falah Husni (LPPM STMIK Lombok, 2018)
Currently the hotspot network used by students in STMIK Lombok uses Basic Service Set topology (BSS), therefore different Service Set Identifier (SSID) in each Access Point (AP) causes the mobility and reliability of the hotspot network to decrease. To overcome this problem can be applied hotspot system with Extended Service Set topology (ESS) that uses more than one AP and integrate all AP into a single wireless network using Internal Wireless Roaming so that client mobility is not disturbed when moving locations in the campus area without having to reconfigured. The signal coverage test of roaming network that has been done in STMIK Lombok using Wireless Distribution System (WDS) has not reached all campus area but can be overcome by adding AP to increase coverage area. Roaming that runs between APs can work but requires more time in the process of moving.